ANATOMICAL AND TOPOGRAPHICAL FEATURES OF THE STRUCTURE OF THE ALVEOLAR PART OF THE MANDIBLE IN PATIENTS WITH PARTIAL ADENTIA - Stupnytskyi, I.R.; Rozhko, M.M.; Stupnytskyi, R.M.; Silenko, Yu.I.; Yeroshenko, G.A. (World of Medicine and Biology, 2021)
The study shows that the thickness of the mucous membrane at the apex of the cellular part of the mandible in patients with defects of the dentition increased in the direction of the teeth that limited this defect. The apex of the cellular part, clearly visible in the oral cavity, did not always coincide with the radiological image of the cellular part, but was formed by a thickened mucous membrane in this area. The shape of the bone base of the cell part repeated the “clinical” type of lateral surfaces and the shape of the apex of the ridge in 87.5±6.8 % of people. Discrepancies were found in types IV and VII of lateral surfaces of the cell process.